2017
DOI: 10.18632/oncotarget.22798
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Specific Peptidase 15 (USP15) suppresses glioblastoma cell growth via stabilization of HECTD1 E3 ligase attenuating WNT pathway activity

Abstract: Expression based prediction of new genomic alterations in glioblastoma identified the de-ubiquitinase Ubiquitin Specific Peptidase 15 (USP15) as potential tumor suppressor gene associated with genomic deletions (11%). Ectopic expression of USP15 in glioblastoma cell-lines reduced colony formation and growth in soft agar, while overexpression of its functional mutant had the opposite effect. Evaluation of the protein binding network of USP15 by Mass Spectrometry in glioblastoma cells uncovered eight novel inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Similarly, Xu et al also demonstrated that USP15 promoted tumor cell invasion and proliferation in glioblastoma 20 . Nevertheless, Oikonomaki et al reported that USP15 suppressed glioblastoma cell growth by attenuating WNT pathway activity, 21 indicating a latent dual role of USP15 as both an oncogene and tumor‐suppressor gene. In addition, USP15 gene amplification was observed in breast and ovarian cancers, indicating that the oncogenic role of USP15 might be prevalent in malignancies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Xu et al also demonstrated that USP15 promoted tumor cell invasion and proliferation in glioblastoma 20 . Nevertheless, Oikonomaki et al reported that USP15 suppressed glioblastoma cell growth by attenuating WNT pathway activity, 21 indicating a latent dual role of USP15 as both an oncogene and tumor‐suppressor gene. In addition, USP15 gene amplification was observed in breast and ovarian cancers, indicating that the oncogenic role of USP15 might be prevalent in malignancies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…S2A–B). To clarify the mechanism underlying AR ubiquitination, the interaction of AR with 6 tumor-suppressive E3 ligases [[22], [23], [24], [25], [26], [27]] including FBXL2, HECTD1, VHL, TRIM13, FBXW7 and SMURF2 were determined. Of that, the AR-FBXL2 interaction was detected after ALZ003 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified HECTD1 as LXN associating protein. Because HECTD1 is an E3 ubiquitin ligase, which widely involved in the regulation of cancer invasion 37,38 , this prompted us to hypothesis that HECTD1 may be related to the ubiquitylation of IκBα. Interestingly, HECTD1 may interact with adenomatous polyposis coli (APC), whose dysfunction has been linked to the development of most forms of colorectal cancer 39 .…”
Section: Discussionmentioning
confidence: 99%